2021
DOI: 10.1016/j.cegh.2021.100815
|View full text |Cite
|
Sign up to set email alerts
|

Assess the knowledge, utilization, level of satisfaction of utilization and barriers of non-utilization regarding Integrated Child Development Services (ICDS) among women of Ernakulam District, Kerala, India

Abstract: The integrated child development scheme (ICDS) was launched in 1975 to provide an integrated package of services to aid the holistic development of the child. The beneficiaries of this scheme are children below the age of six, pregnant and lactating women in the age group of 15-45 years. Objectives: The objectives of the present study were to assess the knowledge, utilization, level of satisfaction of utilization and barriers of non-utilization regarding Integrated Child Development Services (ICDS) among women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…A study by Davey et al ( 41 ), showed that due to lack of easy accessibility of AWC, unavailability of space at the AWC and poor quality of distributed food were some of the major reasons of non-utilization of services ( 41 ). Also, mothers felt difficulty in carrying the child to the AWCs and with not enough contact with the AWC workers makes it more difficult ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Davey et al ( 41 ), showed that due to lack of easy accessibility of AWC, unavailability of space at the AWC and poor quality of distributed food were some of the major reasons of non-utilization of services ( 41 ). Also, mothers felt difficulty in carrying the child to the AWCs and with not enough contact with the AWC workers makes it more difficult ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mothers are the primary care providers and the knowledge about the services provided by ICDS are necessary. In several regions due to lack of awareness the rate of utilization is more ( 20 , 21 ). Around 16% children are low birth weight (16.4%) ( 22 ), and about three-fifth of children are fully immunized ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies[ 16 17 ] also reported a high level of satisfaction of mothers with the services. These findings suggest that there are many within- and between-state variations in the uptake of the ICDS programme and utilisation of services.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Western India reported multiple factors related to household convenience and accessibility of ICDS services influenced their utilization by mothers [ 17 ]. Another study from Southern India in Ernakulam district reported that lack of time, improper communication with AWWs, poor behavior of AWWs, the distance of AWC from home, and lack of knowledge were the main barriers restricting the usage of Anganwadi nutrition services [ 18 ]. A study from Eastern India in the Ganjam District reported the association of factors like socioeconomic status (SES), literacy, and occupation with the extent of ICDS utilization [ 12 ].…”
Section: Discussionmentioning
confidence: 99%